Agricultural credit in a developing economy - Ceylon - Tilakaratna, W. M. (Colombo : Central Bank of Ceylon, 1963)
This book is on agricultural credit which is vital to the problem of development in a primarily agrarian economy like that of Ceylon.
Bibliography: p. [230]-234.
oo 23/01/2019
Loans
Keywords: Agricultural credit